2013
DOI: 10.1590/s0100-40422013000300006
|View full text |Cite
|
Sign up to set email alerts
|

Síntese, caracterização e atividade fotocatalítica de catalisadores nanoestruturados de TiO2 dopados com metais

Abstract: Recebido em 18/4/12; aceito em 9/10/12; publicado na web em 18/2/13 SYNTHESIS, CHARACTERIZATION AND PHOTOCATALYTIC ACTIVITY OF NANOSTRUCTURED TiO 2 CATALYSTS DOPED WITH METALS. Titanium dioxide nanostructured catalysts (nanotubes) doped with different metals (silver, gold, copper, palladium and zinc) were synthesized by the hydrothermal method in order to promote an increase in their photocatalytic activity under visible light. The catalysts were characterized by X-ray diffraction, diffuse reflectance spectros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 22 publications
0
5
0
7
Order By: Relevance
“…The crystal size influences the surface area of the catalyst, this knowledge is very important to surface reactions, the large crystal size may allow direct contact between the metal oxide and the catalytic support, The catalysts were calcinated at 500°C, in general, the crystallization of TiO 2 takes place at temperatures greater than 400 ° C. Silva et al [31] worked with TiO 2 and obtained similar results. Yanan liu et al [32] showed that calcination temperature plays a dominant role in the degree of crystallinity.…”
Section: Structural Characterization Of Cu/tio2 and Cu/al2o3 Catalystsmentioning
confidence: 91%
“…The crystal size influences the surface area of the catalyst, this knowledge is very important to surface reactions, the large crystal size may allow direct contact between the metal oxide and the catalytic support, The catalysts were calcinated at 500°C, in general, the crystallization of TiO 2 takes place at temperatures greater than 400 ° C. Silva et al [31] worked with TiO 2 and obtained similar results. Yanan liu et al [32] showed that calcination temperature plays a dominant role in the degree of crystallinity.…”
Section: Structural Characterization Of Cu/tio2 and Cu/al2o3 Catalystsmentioning
confidence: 91%
“…2021 destacam os Processos Oxidativos Avançados (POA), os quais se baseiam na utilização de espécies altamente oxidantes para promover uma degradação mais efetiva do poluente a ser tratado (BRITO & SILVA, 2012). Dentre os POA, a fotocatálise heterogênea, processo que envolve reações redox induzidas pela radiação que ocorrem na superfície de catalisadores semicondutores, vem sendo amplamente estudada (SILVA & LANSARIN, 2013).…”
Section: Introductionunclassified
“…O dióxido de titânio (TiO 2 ) na fase cristalina anatase é o catalisador mais conhecido e utilizado em processos de fotocatálise heterogênea, na purificação e desinfecção de água e ar. O TiO 2 é um semicondutor fotoelétrico, assim, quando irradiado com fótons de energia (hν) adequada, os elétrons (e⎯) da banda de valência (BV) podem atingir a banda de condução (BC) deixando uma lacuna (h + ) ou buraco na BV [1,2].…”
Section: Introductionunclassified